Study of Confinement of a Column by Carbon Fibre Reinforcement Polymer Mesh - Shinde , Tejal; Kharat , Pallavi; Katkar , Arvind; Bhosale , Akshata; Bhade, Prof B.G (International Journal of Scientific Research in Civil Engineering, 2020)
Carbon fiber reinforced polymers (CFRP) are very attractive to use in civil engineering applications due to its high strength, high durability, corrosion resistance, potentially high elasticity and high tensile strength criteria. This paper deals with Experimental and analytical studies of different parameters on concrete column wrapped with carbon fiber reinforced polymer (CFRP) are taken and investigated. Wrap thickness (l Layer), fiber orientation and the combinations of them were investigated. The results demonstrated significant enhancement in the compressive strength, stiffness and ductility of the CFRP- wrapped concrete column as compared to unconfined concrete column. An analytical model for ultimate stress and strain of confined concrete has been proposed.